1977
DOI: 10.1159/000117607
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Therapeutic Potential of Indoleamine Precursors in Affective Disorders

Abstract: The strategy of loading with precursor amino acids of the monoamines postulated to be involved in the affective disorders is reviewed. Phenylalanine, tyrosine, L-dopa, L-tryptophan and L-5-hydroxytryptophan (L-5HTP) have been found to induce differential behavioural and biochemical effects in both healthy subjects and endogenous depressives. Indoleamine precursors predominantly cause mood changes. However, the efficacy of these amino acids as antidepressants has been neither clearly established nor refuted, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Pretscher (1968) m i Murphy et al (1970 proposed that the platelet is a suitable model to study the process occurring in monoaminergic neurons in the central nervous system. Wirz-Justice et al (1977) suggested that diurnal variations in platelets 5-HT were oppo site in phase to the central 5-HT rhythm. We {Unno et al, 1977) also observed a parallel in crease of the 5-HT level between brain and serum in rabbits administered with various doses of ¿-5-HTP.…”
Section: Discussionmentioning
confidence: 99%
“…Pretscher (1968) m i Murphy et al (1970 proposed that the platelet is a suitable model to study the process occurring in monoaminergic neurons in the central nervous system. Wirz-Justice et al (1977) suggested that diurnal variations in platelets 5-HT were oppo site in phase to the central 5-HT rhythm. We {Unno et al, 1977) also observed a parallel in crease of the 5-HT level between brain and serum in rabbits administered with various doses of ¿-5-HTP.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the circulating levels of these pituitary hormones have been consistently reported after the administration of the serotonin precursors L-tryptophan or 5-hydroxytryptophan to normal controls (for overviews, see Wirtz-Justice 1977;Charney et al 1982). The role of serotonin on the hypothalamo-pituitary-adrenal axis is not clear.…”
mentioning
confidence: 98%
“…Many studies agree that serotonin plays an important role in mood disorders, particularly depression (3)(4)(5)9,10,(18)(19)(20)(21)24,26,28). Today, seroto nin metabolism is well known, and it is also known that its precursor is an essential amino acid: tryptophan (23,25).…”
mentioning
confidence: 99%